2012
DOI: 10.1002/bdd.1805
|View full text |Cite
|
Sign up to set email alerts
|

Variation in omeprazole pharmacokinetics in a random Iranian population: a pilot study

Abstract: Omeprazole is metabolized in the liver mainly by the polymorphic CYP2C19 enzyme. Considerable ethnic differences have been reported in the pharmacokinetics of omeprazole. The present study was conducted to evaluate the pharmacokinetic parameters of omeprazole after a single oral administration to a random Iranian population. Thirty healthy male subjects, aged 24-31 years, weighing 60-98 kg completed the study. Plasma concentrations of omeprazole were measured over a 12 h period after administration of a single… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 36 publications
0
3
0
Order By: Relevance
“…Furthermore, in a study, which was conducted on 30 healthy volunteers, one subject showed a high AUC, half-life and lowest elimination rate compared with mean AUC level. The omeprazole metabolic ratio for this subject was 2.9, while for those of others, it was in the range 0.12-0.56 (Table 8) (Noubarani et al, 2012). In another study by Ala et al.…”
Section: Ppi Pharmacokineticsmentioning
confidence: 46%
See 1 more Smart Citation
“…Furthermore, in a study, which was conducted on 30 healthy volunteers, one subject showed a high AUC, half-life and lowest elimination rate compared with mean AUC level. The omeprazole metabolic ratio for this subject was 2.9, while for those of others, it was in the range 0.12-0.56 (Table 8) (Noubarani et al, 2012). In another study by Ala et al.…”
Section: Ppi Pharmacokineticsmentioning
confidence: 46%
“…It has been proven that each population has characteristic specific pattern of gene polymorphism that extremely affect drug metabolism in that population. The guidelines proposed by the International Conference on Harmonization (1998), suggest the presence of several factors associated with a drug pharmacokinetic to be ethnically sensitive (Committee, 1998;Noubarani et al, 2012). There are large number of reports in the literature speculating the ability of genotyping as an essential tool for safe and wise drug prescribing (Azarpira et al, 2010;Thaker et al, 2017;Vogl et al, 2015).…”
Section: Ppi Pharmacogenomics (With Emphasize On Iran)mentioning
confidence: 99%
“…In Iranian study with 30 healthy volunteers after 20 mg omeprazole single dose, blood samples were collected for 12 hours and omeprazole and 5-hydroxyomeprazole concentrations for pharmacokinetics were measured. 17 Urine concentrations were not studied.…”
Section: Discussionmentioning
confidence: 99%